Museo del Caribe - Salazar-Vargas, Roxy (Instituto Tecnológico de Costa Rica., 2019)
Museo del Caribe Project arises from the intention to revalue the cultural identities of the province of Limón and present a new dynamic that allows the population to be part of the favorable development in its territory. Also, emphasize the important position in the history of our nationʼs development. It became the point of connection between our country and the resto f the world, speeding up the comercial exchanges, mainly of our Golden grain: coffee. So the museum proposes a space in which it exalts its role in Costa Rican development and its identity as a multicultural region. It is located in Barrio Corales I, a high residential area, near the historic center of Limón. The museum is shown as an important point of tourism, attracting economy and cultural Exchange in this area. Its contemporary design is shown as an example of reinterpretation of the Victorian Costa Rican architectural style. So, the identity of Caribbean cultures is captured in the design itself.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019.
Keywords: Costa Rica, Limón; Museos -- Diseño arquitectónico; Cultura afrocaribeña; Arquitectura